Interactive and evolutionary effect of CASZ1 gene variants on varicose veins susceptibility in South Asian Indians - Rohit Mehra; Vikram Patra; Rishi Dhillan; Dattatraya CVNM; Hemender Singh; Love Gupta; Garima Rastogi; Indu Sharma; Varun Sharma (Biological Research)
Abstract Background Varicose veins (VV) are spectrum of common vascular diseases having complex genetic etiology. The Castor Zinc Finger 1 (CASZ1) gene has been involved in vascular development and its variant has shown association with VV in various ethnicities, but CASZ1 susceptibility to VV risk is unexplored in the South Asian Indian population. The objective of this study was to estimate the association of the CASZ1 gene variations and VV susceptibility in the South Asian Indians, and to examine the evolutionary patterns of these variants compared to other populations. Methodology Population based case control analysis was conducted on all CASZ1 variants present in the Global Screening Array, including the established VV variant rs11121615 with a focus on validating and identification of both novel and established genetic markers to capture a full spectrum of population-specific genetic markers unique to studied population group. Linkage disequilibrium patterns and cumulative variant effects were also analyzed, followed by selection pressure assessment using neutrality tests. Results Three CASZ1 variants rs72860191 (OR 1.58, 95% CI 1.07–2.32, p = 0.01), rs7519604 (OR 1.43, 95% CI 1.05–1.94, p = 0.01), and rs11121615 (OR 0.69, 95% CI 0.50–0.95, p = 0.02) were observed to be significantly associated with VV. Haplotype analysis identified unique haplotype structure of South Asian Indians compared to other global populations. Moreover, the cumulative OR was observed to be higher than the independently estimated values (OR = 2.41, 95% CI 1.48–3.94), indicating genotypic epistasis of VV associated variants. The neutrality tests revealed balancing selection within CASZ1 in the studied population compared to other populations, Conclusion The present study identified CASZ1 variants and their epistatic interactions is associated with VV susceptibility supported with evidence of balancing selection, provides crucial insights into the genetic architecture of VV in studied group, highlighting the impact of evolutionary forces on disease susceptibility.